2012
DOI: 10.31018/jans.v4i1.219
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and detection of parasitic infections by cyst and ova on fruits and vegetables from different major markets in Kogi, Nigeria

Abstract: Abstract:In the course of a study of parasitic infections by cyst and ova on fruits and vegetable sold in middle-belt Nigeria, three different major public markets was selected. Six different fruits and vegetables total to 2406 samples were examined.Data obtained were statistically analyzed using anova for the level of significance difference where appropriate. Of the 1755 fruits examined, 4.3% were positive for parasites ova and 2.5% for cysts. Of the 761 vegetables examined, 4.6% were positive for parasites … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 2 publications
0
8
0
Order By: Relevance
“…Contrarily, Hassan et al . (2012) and Omowaye and Audu (2012) showed no difference between the contamination rates found at the various markets; this could be explained, in part, by the various sources from which vegetables are brought to these markets.…”
Section: Literature Selection Criteriamentioning
confidence: 83%
See 2 more Smart Citations
“…Contrarily, Hassan et al . (2012) and Omowaye and Audu (2012) showed no difference between the contamination rates found at the various markets; this could be explained, in part, by the various sources from which vegetables are brought to these markets.…”
Section: Literature Selection Criteriamentioning
confidence: 83%
“…Furthermore, Lass et al (2012) proved that the cultivation of vegetables in farms where the contact with feline feces is more probable increase the risk of contamination with T. gondii. Contrarily, Hassan et al (2012) and Omowaye and Audu (2012) showed no difference between the contamination rates found at the various markets; this could be explained, in part, by the various sources from which vegetables are brought to these markets.…”
Section: Vegetables' Sourcementioning
confidence: 83%
See 1 more Smart Citation
“…Fruits and vegetable contamination by multiple parasite species observed in this study might indicate the possibility of high-level contamination of fruits and vegetables, which perhaps results in multiple parasitic infections in humans (Bekele et al, 2017). It might also indicate the persistence of intestinal parasitic infections in the area (Omowaye & Audu, 2012). The detection of these geohelminth and protozoancysts, ova/ larvae on fruits and vegetables in the studied markets, has a significant public health implication (T Auta et al, 2017).…”
Section: Discussionmentioning
confidence: 73%
“…This finding was similar to previous reports in Alexandria, Egypt(El Said Said, 2012), and in Ardabil, Iran (Daryani, Ettehad, Sharif, Ghorbani, & Ziaei, 2008), where the contamination rates were (31.7%)and (29%), respectively. Lower rates of contamination in the Middle East were detected in Riyadh, Saudi Arabia (16.2%) (Al-Megrin, 2010); and Burdur, Turkey (6.3%) (Adanir & Tasci, 2013).Higher contamination rates were detected in Bahir Dar City, Northwest Ethiopia(39.1%) (Alemu et al, 2020); Dire Dawa, Eastern Ethiopia (Endale, Tafa, Bekele, & Tesfaye, 2018); Arba Minch, Southern Ethiopia (54.4%) (Bekele et al, 2017); Kogi state, Nigeria (Omowaye & Audu, 2012); Jimma town, southwest Ethiopia (Tefera et al, 2014); and Jimma Town, Southwest Ethiopia (Tefera et al, 2014); Ghana (36%) (Amoah, Drechsel, Abaidoo, & Ntow, 2006); Jos, Nigeria (36%) (Damen et al, 2007); Tripoli, Libya (58%) (Abougrain, Nahaisi, Madi, Saied, & Ghenghesh, 2010); and Kisli, Kenya (75.9%) (Nyarango et al, 2008) (Nyarango, Aloo, Kabiru, & Nyanchongi, 2008; and the highest rate was detected in Khorramabad, Iran (79%) (Ezatpour, Chegeni, Abdollahpour, Aazami, & Alirezaei, 2013).…”
Section: Discussionmentioning
confidence: 99%